Alteration of salivary Streptococcus is associated with statin therapy in older adults: a cohort study - Hisamatsu, Daisuke; Ogata, Yusuke; Suda, Wataru; Mabuchi, Yo; Naraoka, Yuna; Yamato, Taku; Ikeba, Akimi; Kumagai, Kyoko; Hattori, Masahira; Akazawa, Chihiro (Frontiers in Pharmacology, 2025)
BackgroundSalivary microbiome alterations are associated with chronic diseases, such as cardiovascular disease, diabetes, and dementia. These chronic diseases often coexist in older adults, leading to polypharmacy. This situation complicates the relationship between systemic diseases and salivary microbiome dysbiosis. Previous studies have demonstrated the association of the human gut microbiome with common prescription drug use, including polypharmacy. However, a comprehensive analysis of the salivary microbiome and prescription drugs is yet to be conducted in older adults. Therefore, in this study, we performed a multivariate analysis to investigate the relationship between salivary microbiomes and host variables, including prescribed drugs, cognitive function, and oral health, in Japanese older adults with different disease backgrounds.MethodsWe enrolled non-hospitalised 82 older adults aged ≥70 years from a Japanese village community, and collected metadata, including age, sex, body mass index, cognitive function, oral health, alcohol consumption, smoking, and common prescription drug information. We performed multivariate analyses and functional predictions on the salivary microbiome based on 16S ribosomal RNA gene amplicon sequencing, including the metadata as potential confounders.ResultsWe observed a relationship between the human salivary microbiome and prescribed drug use in Japanese older adults with a heterogeneous background of comorbidities. The effects of several prescribed drugs, such as statins, proton pump inhibitors, and transporter/symporter inhibitors, on the salivary microbiome diversity were more prominent than those of host variables, including age, sex, and oral health. Notably, statin use was strongly correlated with a decrease in the Streptococcus abundance. Furthermore, statin intensity and obesity may be associated with altering the salivary microbiome, including functional predictions for vitamin biosynthesis and purine nucleotide degradation pathways in statin users.ConclusionOur multivariate analysis, adjusted for prescribed drug use and non-use, revealed the drug-specific alteration of salivary microbiome composition in Japanese older adults with comorbidities. To our knowledge, this study is the first to described the association of common prescription drug use with salivary microbiome alterations in older adults. Our findings indicated that prescribed drug use is a key factor in understanding the link between salivary microbiome changes and systemic diseases in older adults.